Business management perspectives on the circular economy: Present state and future directions - Ahmad Farhan; Bask Anu; Laari Sini; Robinson Craig (Elsevier, 2025)
Circular economy (CE) is an economic model designed to substitute the take-make-dispose linear economy with a regenerative system. Business management has a critical role in translating CE into practice. Extant management research on CE, while expanding rapidly, remains fragmented and lacks a holistic perspective. Through bibliographic coupling, a technique that identifies emergent research trends rather than past traditions in literature, we analyse the current state of CE research in business management and develop an agenda for future research. Six streams emerge: strategy, learning and innovation, consumer behaviour and remanufacturing, supply chains and implementation, circular business models, industrial symbiosis, and emerging technologies. Through content analysis we explore research trends and gaps, providing a more comprehensive overview of CE management research than prior studies. Moreover, we identify promising paths for future research, focused around three overarching research questions that provide a platform to accelerate the impact of business and management research on the adoption and proliferation of CE practices in future.